Virtues in Iamblichus and the Shift of Paradigm - Magoulas, Ch. (SCHOLE, 2010)
This paper aims at pointing out differences between the perception of virtues in Plato’s Protagoras and especially the Symposium and in Iamblichus. The argument is focused on the fact that, although both philosophers agree that virtues can be taught and they are therefore a social activity, in Plato there is a certain significance laid on the social role of virtues as well as on the cardinal importance of love as a sentiment that leads to temperance, in Iamblichus, what is more adequate for a philosopher to exercise is rather the hieratic values, while the temperance is the virtue that leads to the union with god. Based on that argument and in the fact that theurgy as a practice is more personal than social, we could possibly trace in representative philosophical thoughts of these eras the change of worldviews between classical and late antiquity, as, at any rate, the historical research shows.